Paclitaxel triggers molecular and cellular changes in the choroid plexus - Zamani, Alemeh; EmamiAref, Parisa; Kubíčková, Lucie; Hašanová, Klaudia; Šandor, Ondřej; Dubový, Petr; Joukal, Marek (Frontiers in Pain Research, 2024)
Paclitaxel is a widely used chemotherapeutic agent for treating various solid tumors. However, resulting neuropathic pain, often a lifelong side effect of paclitaxel, can limit dosing and compromise optimal treatment. The choroid plexus, located in the brain ventricles, spreads peripheral inflammatory reactions into the brain. Our study is the first to analyze the effects of paclitaxel on inflammatory alterations in the choroid plexus. We hypothesized that the choroid plexus could respond directly to paclitaxel and simultaneously be indirectly altered via circulating damage-associated molecular patterns (DAMPs) produced by paclitaxel application. Using immunohistochemical and Western blot analysis, we examined the levels of toll-like receptor 9 (TLR9) and formyl peptide receptor 2 (FPR2), along with the pro-inflammatory cytokines interleukin 6 (IL6) and tumor necrosis factor α (TNFα) in choroid plexus epithelial cells of male Wistar rats following paclitaxel treatment. Moreover, we utilized an in vitro model of choroid plexus epithelial cells, the Z310 cells, to investigate the changes in these cells in response to paclitaxel and DAMPs (CpG ODN). Our results demonstrate that paclitaxel increases TLR9 and FPR2 levels in the choroid plexus while inducing IL6 and TNFα upregulation in both acute and chronic manners. In vitro experiments further revealed that paclitaxel directly interacts with epithelial cells of the choroid plexus, leading to increased levels of TLR9, FPR2, IL6, and TNFα. Additionally, treatment of cells with CpG ODN, an agonist of TLR9, elicited upregulation of IL6 and TNFα. Our findings determined that paclitaxel influences the choroid plexus through both direct and indirect mechanisms, resulting in inflammatory profile alterations. Given the pivotal role of the choroid plexus in brain homeostasis, a compromised choroid plexus following chemotherapy may facilitate the spread of peripheral inflammation into the brain, consequently exacerbating the development of neuropathic pain.